Flexural Behaviour of Hybrid Concrete Beam-Column Connections Under Static and Repeated Loads. Issue 1 (August 2021) - Mosheer, Khamail Abdul-Mahdi; Dawood, Mustafa B; Ghalib, M H
Abstract: The present study includes an experimental investigations for the behavior and the load carrying capacity of hybrid beam-column connections subjected to static and repeated loading condition. The goals were to evaluate the effect of using slurry infiltrated fiber concrete (SIFCON). Experimental program consists of testing six beam-column connections, two of them casted with normal concrete and the other using SIFCON in crtical section in addation to normal concrete. Also, the program testing three of connection subjected to static load and the similar other subjected to repeated loads. Results show an improve in flexural behavior for specimens with SIFCON as compared with normal concrete under static and condition, on the other hand, the reduction in flexural strength when was exposed to repeated loads in comparison with that under static loads reach 2.6% at hybrid connection. While, the reduction was increased to 5.1% for the specimen without SIFCON.